Perceptions and Challenges of Using Web-based Platforms for English Language Learning among Senior High Students - Eka Surya Fitriani; Sisi Rosida; Rizky Vita Losi; Lestari Sylvana (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explored the perceptions and challenges faced by senior high school students in utilizing web-based platforms for English language learning. Employing a literature review methodology, the study synthesized findings from recent studies to analyze the effectiveness, user experiences, and obstacles associated with digital learning tools in the context of language education. The study highlighted students' positive attitudes towards the accessibility and interactive features of web-based platforms while identifying challenges such as technical difficulties, limited digital literacy, and motivational issues. The review also examined the pedagogical implications of integrating web-based platforms into traditional learning environments, emphasizing the need for teacher training and support mechanisms to maximize learning outcomes. By providing a comprehensive overview of existing research, this study aimed to contribute to the discourse on leveraging technology for language learning in senior high schools and offers insights for future research and policy development.